Factors influencing school nurse service utilization in selected schools of Kathmandu district: a mixed method study - Sharma, Saraswati; Bhandary, Shital (Journal of General Practice and Emergency Medicine of Nepal, 2022)
Introduction: One school one nurse is a new program in Nepal aiming to improve students’ health. This study aimed to find utilization of school nurse service and associated factors in selected schools of Kathmandu district using mixed methods approach. Method: Study included Kirtipur Secondary School and Shivapuri Higher Secondary School. It used concurrent triangulation mixed method design. Quantitative phase included survey among 30 students, 15 from each school while qualitative phase had 4 in-depth interviews and 2 key informant interviews. Fisher’s exact test and Braun and Clarke’s six-step thematic analysis based on socio-ecological model were used to analyze factors associated with service utilization quantitatively and qualitatively. Results were triangulated using convergent, divergent and expansive findings. Result: Out of 30 participants, 27(90%) had ever contacted to school nurse for any health issue. Student’s visit to school nurse for mental health issue was the only factor found significantly associated with frequency of visit. Qualitative analysis explored many associated factors at different socio-ecological level. No sex wise variation in sharing sensitive health issue with school nurse was convergent finding. Divergent findings were identified regarding factors like health issues to visit school nurse, motivator, perceived privacy and sex. Expansive finding was that a school nurse appointed in a school also served nearby schools beyond her job description. Conclusion: An effort from individual level to policy level is needed to resolve hindering factors of school nurse service utilization and maintain the promoting ones.